Spherical analysis on homogeneous vector bundles of the 3-dimensional euclidean motion group - Díaz Martín, Rocío Patricia; Levstein, Fernando (2024)
Artículo finalmente publicado en: Díaz Martín, R. y Levstein, F. (2018). Spherical analysis on homogeneous vector bundles of the 3-dimensional euclidean motion group. Monatshefte fur Mathematik, 185 (4), 621-649. https://doi.org/10.1007/s00605-017-1123-1